Effects of Instability Resistance Training on Physical and Cognitive Function in Adults - Cavalcante, Bruno Remígio; Falck, Ryan Stanley; Silva, Dayane Tays; Campos, Igor Rafael Andrade; Silva, Mateus Santos; Eckardt, Nils; Batista, Gabriel Amorim; Ferreira, Fabiano Moura; Pirauá, André Luiz Torres; Souza, Mariana Ferreira de; de Araujo, Rodrigo Cappato (International Journal of Sports Medicine, 2025)
Resistance training is an effective strategy for combating geriatric syndromes, including frailty, sarcopenia, and cognitive impairment. Performing instability resistance training (IRT) (e.g., weight-bearing, machine-based, or free-weight exercises using unstable surfaces) may provide additional benefits on health outcomes in middle-aged and older adults. With this in mind, we examined the impact of IRT on physical and cognitive functioning (primary outcomes), fall risk, and quality of life (secondary outcomes). We searched three specific databases from inception to October 2024. We included peer-reviewed, randomized trials that analysed the effects of intervention on outcomes of interest among adults aged 50 years or older. Risk of bias and quality of reporting were ascertained using validated checklists. We performed a random-effects meta-analysis using robust variance estimation. 18 studies with participants from Brazil, Spain, Germany, and South Korea (n=528, %women: 35–100%) were included in the qualitative review, and 12 studies in the meta-analysis. We found that IRT had a medium-to-large-sized effect on physical and cognitive functioning. Studies had a high quality of reporting but presented significant heterogeneity and low-to-moderate risk of bias. Our findings suggest that IRT is a promising strategy for promoting physical and cognitive benefits in middle-aged and older adults.
Keywords: exercise training; rehabilitation; mobility; cognitive function; ageing